Karakteristik Pengembangan Wilayah Sebelum dan Sesudah Pemekaran Kabupaten Jayapura - Agustinus Kaeng Udiarto (Jurnal Wilayah dan Lingkungan, 2015)
The regional development issue in Jayapura cannot be separated from the issue of regional split. The regional split in Jayapura District is expected to generate job opportunity, to reduce poverty, to improve the availability of adequate infrastructures, to equalize the distribution of population, and to accelerate the regional development process. This study aims to determine the development of Jayapura District before and after the regional split between 2002 and 2012. The analysis is limited to economic, social, demographic and infrastructures aspects. The study is conducted by using a quantitative method through comparative analysis. The results show that the Jayapura District has not quite successfully to develop after the regional split happened. The regional development of Jayapura District has not significantly influenced the economic and social demographic aspects since the unemployment rate, and the ratio of teachers to students have a negative tendency. However, the infrastructure aspect has a positive impact on the regional development characterized by the increasing number of and condition of infrastructures, especially education and health facilities. Therefore, it can be concluded that the development of the region can be successful if there is a positive trend of economic, social demographic, and infrastructure aspects.